Observational Study of bacteria causes Nosocomial Infection in an intensive care unit in Al-Brega General Hospital - Suliman. Fathi. Alsdig (Journal of Libyan Academy Bani Walid, 2025)
This observational study aimed to identify the bacterial causes of nosocomial infections among patients admitted to the Intensive Care Unit (ICU) of Al-Brega General Hospital. A total of 500 patients admitted between August 2024 and January 2025 were monitored for the development of hospital-acquired infections. Clinical data were collected, and bacterial cultures were obtained from various clinical sites to determine the pathogens responsible for these infections. The findings revealed that nosocomial infections occurred in 27% of ICU patients, with Staphylococcus aureus being the most prevalent pathogen (24.8%), followed by Escherichia coli (15.8%). Rifampin demonstrated the highest antibacterial efficacy, whereas 95.8% of the isolates showed resistance to commonly used antibiotics, underscoring a major therapeutic challenge in infection management. These results emphasize the urgent need for robust infection control practices and the implementation of antibiotic stewardship programs within ICU settings to reduce infection rates. Furthermore, continuous surveillance of bacterial pathogens and antimicrobial resistance patterns is crucial to enhance patient outcomes and to inform evidence-based treatment strategies in critical care environments.